Hubungan Self Efficacy dan Dukungan Sosial dengan Kematangan Karir Siswa Kelas XI di SMK Negeri 2 Padang - Alfiqul Rahmatia Idaman; Isna Syahrina; Herio Dewinda (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2021)
This study aims to see the relationship between self-efficacy and social support with the career maturity of grade XI students at SMK Negeri 2 Padang. The research design used in this study is a quantitative method. The population of this research was 167 students of class XI at SMK Negeri 2 Padang and the sampling technique used was random sampling technique. Test the validity and reliability of this study using Alpha Cronbach technique. The results of the validity coefficient on the career maturity scale moved from rix = 0.305 to rix = 0.627 with a reliability coefficient of α = 0.895, while on the self-efficacy scale it moved from rix = 0.359 to rix = 0.795 with a reliability coefficient of α = 0.912. And the scale of social support moves from rix = 0.311 to rix = 0.669. Based on data analysis, it was obtained a value of 0.240 with a significance level of 0.008 which means it is accepted. This shows that there is a significant relationship between self-success and social support with the career maturity of class XI students at SMK Negeri 2 Padang. The effective suggestion from the variable of independence and social support with the career maturity of class XI students at SMK Negeri 2 Padang was 58%